Perfect secrecy cryptosystem with nonuniform distribution of keys - Chuanjun TIAN (Tongxin xuebao)
More strictly mathematical concepts of infinite perfect secrecy and random “one-time pad” cryptosystem in theory were presented,and the whole secure communication system was divided into two stages:design of a basic cryptosystem and one of its applications.How to design a basic cryptosystem by using a group of orthogonal Latin squares was first studied and an example to illustrate how to design nonlinear encryption transformations for a basic cryptosystem was given.Then,how to design the sequence of keys by using random method with nonuniform distribution was discussed,and it was strictly proven in theory that the infinite random “one-time pad” cryptosystem based on the designed basic cryptosystem was of perfect secrecy.Since the obtained result generalizes the existing one for random “one-time pad” cryptosystem to be perfect by using a basic cryptosystem with modulo addition,it may be used as a wider ideal simulated prototype to design stream cipher algorithms.Since the number of basic cryptosystems that can be designed is much more than one of the common basic cryptosystems with modulo addition,the obtained result is effective supplement and perfection to mainstream design method for the current stream cryptosystems.